Dziennikarze i politycy. Blisko, coraz bliżej - Piechocki, Marcin (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The relations between the media and political systems are of particular importance for Polish democracy, which is a mere twenty years old. The modern media landscape involves elements of the breaking of journalistic standards, the politicization and subordination of the public media to a particular party, commercial media support for political parties, local government institutions publishing their own press releases, and journalists on election lists. Aware of the influence the media may have on the social perception of politics, political actors treat the media instrumentally, knowing that they can be used to make voters aware of their existence. It is particularly dangerous for the media to support defined political forces because the price of such support remains unknown. The issue of the public media needs to be urgently resolved. If the legislator acknowledges the need for them to operate, they need to be ensured appropriate financing and independence. If such a need is not perceived, Polish Television and Polish Radio should be privatized. Voters and recipients of the media need to realize that objective journalism may be an ideal, but this does not release media workers from the requirement of maintaining their professional integrity. Separating information from commentary and presenting the arguments of all sides in political disputes are a standard to be required of all mass media.